3D full-wave optical and electronic modeling of organic bulk-heterojunction solar cells : a predictive approach - Koh, Wee Shing (2014)
A predictive approach using 3D full-wave optical and electronic modeling of an organic bulk-heterojunction photovoltaic device (P3HT:PCBM) is presented. The optical part is modeled by solving 3D frequency domain Maxwells equations such that the scattering of subwavelength nanostructures can be modeled accurately. The electronic simulation which consists of solving the rate equations to account for the generation and recombination of polarons or charges, and the flow of electrons and holes are assumed to be drift-diffusion in nature. Here, nanoparticles with subwavelength sizes are added to the P3HT:PCBM photovoltaic device and the current-voltage behavior is predicted by the model.